PENANGANAN PASCA PANEN DAN DIVERSIFIKASI PENGOLAHAN BUAH MANGGIS DI DESA BELIMBING KECAMATAN PUPUAN KABUPATEN TABANAN - SELAMET DUNIAJI, AGUS (Buletin Udayana Mengabdi, 2014)
Mangosteen fruit in the village of Belimbing at the time of harvest and the season is very abundant and the price at that time was very low, so farmers often lose money. Therefore, farmers need to be equipped with skills mangosteen fruit post-harvest handling and processing method. Mangosteen fruit contains vitamin C is high at 66.0 mg/100 g of material and also contains antioxidants like xanthon very useful and good for health. Mangosteen fruit processing training was conducted at Women Farmers Group (KWT) at Duren Taluh, Belimbing of Pupuan district ofTabanan. Number of participants is 35 people. Training was conducted in March 2013 held at the Hall of subak groups Duren Taluh Belimbing. Diversification offood processingin addition toreproducea varietyof processedfoods thatcanalsoextendthe shelf life ofthe productand thetype of processingcan still beobtainedin theoff-season. Syrup and juice products produced in the hamlet village Duren Taluh is expected to overcome the problems of post-harvest handling and processing the mangosteen fruit and can increase the income of farmers and farming groups of women in villages of Belimbing of Pupuan district ofTabanan. Keywords: Mangosteen fruit, syrup, juice, women farmers group